Construction of Two-Way Volume Table of Eucalyptus Tereticornis for Mid-Himalayan Region of Himachal Pradesh - Kumar, Ishant; Gupta, R. K.; Kumar, Arun (International Journal of Bio-resource and Stress Management, 2020)
Eucalyptus is the genus of trees that is most planted around the world because of its large number of species, the ability to adapting in many different sites, and the possibilities of producing wood for many different uses. The present study was conducted to construct the two-way volume table of Eucalyptus tereticornis for mid-Himalayan region of Himachal Pradesh. For the purpose, secondary data for diameter and height of Eucalyptustrees were collected from four different sites viz. Khaltoo,Ucchagaon, Kharkog and Pandah. From each plantation site,150 trees of Eucalyptus tereticorniswere selected and the data were subjected to variability analysis in order to test the variability among different sites. Bartlett’s chi-square test for testing the homogeneity of variances suggested that there were no variability with respect to DBH, height and volume among different sites. Site wise comparison was also performed to test the equality of means among different sites. Maximum mean diameter (m) was observed at Khaltoo (0.2097) and minimum was observed at Ucchagaon (0.1767). Mean height (m) was observed maximum in Kharkog (10.6374) and minimum in Pandah (9.7873). Maximum mean volume (m3) was recorded at Khaltoo (0.3955) and Minimum mean volume was recorded at Ucchagaon (0.2105) which was statistically at par with Kharkog (0.2815).Regression analysis was performed to estimate the volume of Eucalyptus trees using ordinary least square estimation method. For the construction of two way volume table,linear model (V=0.0003+0.7842 D2H) was observed best fit on the basis of highest R2 value (0.96) and least root mean square error value (0.0282). These models may be used for the construction of volume table.